Eupalitin induces apoptosis in prostate carcinoma cells through ROS generation and increase of caspase‐3 activity. (12th November 2015) - Kaleem, Sarjeel; Siddiqui, Sahabjada; Siddiqui, Hefazat Hussain; Badruddeen,; Hussain, Arshad; Arshad, Mohammad; Akhtar, Juber; Rizvi, Aleza
Abstract: Prostate cancer is the second most common malignancy in the human reproductive system. Eupalitin is one of the O‐methylated flavonol‐exhibited enhanced cancer chemopreventive agents. The current study highlights the structural determination of eupalitin and aims to explore the antitumor activity of eupalitin in human prostate cancer cell (PC3) and its underlying mechanism. Eupalitin structure was determined by using FTIR, 1 H NMR, and 13 C NMR. PC3 cells were treated with increasing concentrations of eupalitin, followed by analysis of the cell viability with an MTT assay. The results demonstrated that eupalitin markedly inhibited the proliferation of PC3 cells in a concentration‐dependent manner. The results from fluorescent microscopic analysis of nuclear condensation and intracellular ROS generation determined that eupalitin significantly induced ROS level lead to nuclear apoptosis. Cell cycle analysis revealed that eupalitin‐induced cell cycle progression as a percentage of cells in G0/G1 phase decreased whereas S phase increased. Caspase‐3 immunofluorescence analysis confirms the efficacy of eupalitin‐inducing apoptotic pathway and cell death. Thus, our study is helpful in understanding the mechanism underlying these effects in prostate cancer and it may provide novel molecular targets for prostate cancer therapy.